The structure and stability of coping with low-control stressors - Buško, Vesna (Array, 2003)
The study examines the latent structure of coping responses within typically low-control situational context. Self-report measures of the sources of stress and 11 situation-specific coping strategies were taken in a sample of recruits attending military basic training. Data gathering procedures were done at the very beginning (N=445), and by the end (N=421) of the basic training. Support was found via confirmatory factor analyses for a three-factor model of coping that included the dimensions of problem solving strategies, emotion-focused strategies, and the strategies aimed at acceptance of situation. Correlations between the scores on the corresponding latent coping dimensions point to a moderately high stability of coping over the five-week period, ranging from .67 for the acceptance of situation to .75 for the problem solving factor.